2004
DOI: 10.1038/modpathol.3800117
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of metastatic melanoma in nonsentinel nodes and clinical outcome based on the primary melanoma and the sentinel node

Abstract: Lymphatic mapping and sentinel node biopsy are well-established techniques for staging and managing patients with melanoma, breast cancer and other malignancies that spread initially to the regional lymph nodes. Identification of tumor in the sentinel node is the most precise staging technique currently available. The sentinel node is the site of metastatic melanoma in approximately 20% of melanoma patients and if tumor is present in the sentinel node it is customary to perform a complete dissection of the lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 32 publications
4
89
3
1
Order By: Relevance
“…Our aim was to identify variables easy to measure and reproducible to combine at the hope to identify clinically useful predictors of NSLN involvement and significant on OS. For that reason, we did not include in our analysis the SLN tumour burden, even if many studies have found the size of the metastatic deposits in the SLN to be predictive of NSLN involvement [7], [9], [10] and [11]. Also recently, Cadili et al [21] confirmed the prognostic relevance of SLN total tumour size on both NSLN involvement and disease course in a large melanoma patient cohort.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our aim was to identify variables easy to measure and reproducible to combine at the hope to identify clinically useful predictors of NSLN involvement and significant on OS. For that reason, we did not include in our analysis the SLN tumour burden, even if many studies have found the size of the metastatic deposits in the SLN to be predictive of NSLN involvement [7], [9], [10] and [11]. Also recently, Cadili et al [21] confirmed the prognostic relevance of SLN total tumour size on both NSLN involvement and disease course in a large melanoma patient cohort.…”
Section: Discussionmentioning
confidence: 84%
“…In our experience, the number of positive SLNs was not associated to an increasing NSLN involvement, whilst the prognostic relevance of Starz classification was ascertained in univariate but not confirmed in multivariate logistic regression analysis. The predictive value of Breslow thickness on NSLN involvement has been found in some previous papers, but not confirmed by others [10], [13], [14], [15], [20], [31] and [33]; the same happens for ulceration, thus confirming a great deal of variability which limits the drawing of definite conclusions. Some studies suggested also to consider the association of two or more variables.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…They observed that the SLNs were more affected than the non-SLNs and suggested that there may be a direct effect of tumor or tumor-associated factors on DC maturation and function. They also showed that a higher frequency of DCs in SLNs was correlated with reduced likelihood of recurrence and death from melanoma (34). The marker they used in that study (S100) identifies DCs at different stages of maturation, including mature DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In melanomas, it was suggested that invasion of lymph nodes by tumor cells results in suppression of lymph node functions with alterations in immune cell ratio and activity (20,25,33). Cochran et al reported that the paracortex of lymph nodes with melanoma metastases contained decreased numbers of DCs (33,34) that were phenotypically less mature as compared with DCs in nonmetastatic lymph nodes (33). They observed that the SLNs were more affected than the non-SLNs and suggested that there may be a direct effect of tumor or tumor-associated factors on DC maturation and function.…”
Section: Discussionmentioning
confidence: 99%